Larval rearing of kelabau fish Osteochilus melanopleurus, Bleeker 1852 with different live feed - Asiah, Nur; Aryani, Netti; Heltonika, Benny (Jurnal Akuakultur Indonesia, 2024)
This study aimed to determine the effect of different starting feeds on the growth and survival rate of kelabau fish larvae (Ostechilus melanopleurus, Bleeker 1852). The research was conducted in a Complete Randomized Design (CRD), 3 treatments and 3 replicates. The tested animals used were 7-Dpc (Day post hatch) 90 kelabau fish (Ostechilus melanopleurus) larvae with an initial average length of 0.50 ± 0.06 cm and an initial weight of 0.03 ± 0.02 g. Treatment of one (P1) Artemia nauplii, (P2) Tubifex sp., and (P3) Daphnia. Aquarium research containers size 30×30×20 cm3 9 pieces with a volume of 5 L of water without water flow in the first week onwards from the second week to the 4th week are increased to 10 L with a water recirculation system with a water flow of about 0.5 L per minute. Measurement of the length and weight of the larvae is carried out once a week for 4 weeks. The results showed that the highest length and weight growth was obtained in the P2 treatment of 3.92 ± 0.13c cm and 1.25 ± 0.03c g, and the lowest growth was in the P3 treatment of 1.73 ± 0.05a cm and 0.093 ± 0.010a g. The ANOVA results showed that feeding Tubifex sp. had a very noticeable different effect with a value of P<0.01. Keywords: feed type, Osteochilus melanopleurus, growth ABSTRAK Penelitian ini bertujuan untuk mengetahui pakan awal berbeda terhadap pertumbuhan dan kelulushidupan larva ikan kelabau (Ostechilus melanopleurus, Bleeker 1852). Metode Penelitian yang digunakan adalah metode eksperimen, dengan Rancangan Acak Lengkap (RAL), 3 perlakuan dan 3 ulangan. Hewan uji yang digunakan adalah larva ikan kelabau (Ostechilus melanopleurus, Bleeker 1852) umur 7 hari sebanyak 90 ekor dengan rata-rata panjang awal 0,50 ± 0.06 cm dan berat awal 0.03 ± 0.02 g. Perlakuan satu (P1) Nauplii Artemia, (P2) Tubifex sp. dan (P3) Kutu Air. Wadah penelitian akuarium ukuran 30×30×20 cm3 9 buah dengan volume 5 L air tanpa aliran air pada minggu pertama dan seterusnya dari minggu kedua sampai minggu ke 4 ditambah menjadi 10 L dengan sistem resirkulasi air dengan aliran air sekitar 0.5 L per menit. Pengukuran panjang dan bobot larva dilakukan seminggu sekali, selama 4 minggu. Hasil penelitian menunjukkan bahwa pertumbuhan panjang dan berat tertinggi ditunjukkan pada perlakuan P2 sebesar 3.92 ± 0.13c cm dan 1.25 ± 0.03c g, dan pertumbuhan terendah yaitu pada perlakuan P3 1.73 ± 0.05a cm dan 0.093 ± 0.010a g. Hasil ANOVA menunjukan bahwa pemberian pakan Tubifex sp. memberikan pengaruh berbeda sangat nyata dengan nilai P<0.01. Kata kunci: Osteochilus melanopleurus, pertumbuhan, tipe pakan